مساهمة في دراسة تأثير الألياف الفولاذية على سلوك البيتون عالي المقاومة - تريكية, علي; منصور, نزيه; نوح, علي (Latakia University Journal -Engineering Sciences Series, 2017)
يتضمن البحث دراسة تجريبية لتأثير الألياف الفولاذية على المتغيرات الأساسية لمخطط الإجهاد- تشوه للبيتون عالي المقاومة على الضغط البسيط، أي على: شكل مخطط الإجهاد- تشوه، معامل مطاوعة البيتون،قدرة المادة على امتصاص الطاقة.لهذه الغاية تم تحضير مجموعة من العينات البيتونية الاسطوانية بمقاومة على الضغط(70 MPa). تمت إضافة الألياف الفولاذية ذات نسبة الشكل 70=L/D بأربع نسب حجمية مختلفة للخلطة البيتونية وهي: (0-1-1.5-2)%. اختبرت الاسطوانات تحت تأثير التحميل المستمر على الضغط وتم الحصول من خلال نتائج الاختبارات على المنحني الكامل لمخطط الإجهاد- تشوه. أظهرت النتائج التجريبية للبحث وجود تاثير إيجابي ملحوظ للألياف الفولاذية على سلوك البيتون عالي المقاومة ويزداد هذا التأثير كلما زادت كمية الألياف الفولاذية في الخلطة. يظهر ذلك في مخطط الإجهاد- تشوه، حيث أن الجزء الصاعد يتغير بشكل طفيف، بينما الجزء الهابط يتغير بشكل كلي ويقل انحداره بزيادة كمية الألياف الفولاذية، وبالتالي تحسين مطاوعة البيتون عالي المقاومة وقدرته على امتصاص الطاقة، وبذلك يبتعد سلوك البيتون عالي المقاومة عن السلوك الهش.This research presents an experimental study about the effect of steel fibers on the main variables of stress- strain curve for high strength concrete on simple compression, which are: shape of stress- strain curve, ductility factor, energy absorption capacity. For this purpose, series of cylinders concrete specimens were prepared in compressive strength (70 MPa). the steel fiber with aspect ratio of L/D =70 were added at the volume fractions of (0-1-1.5-2)%. The cylinders were tested under a monotonic loading at compression, and as a result of the tests, the total curve of stress- strain was obtained. The experimental results of research showed a positive effect of steel fibers on the behavior of high strength concrete, this effect increased with increasing volume fraction of steel fibers. It can be seen from stress-strain curve, whereas the slope of the ascending branch is not much affected. The descending branch of the stress- strain curve decreases by the increase in the fiber volume fraction. This means the ductility and toughness improve with the addition of steel fibers and as a result the behavior of high strength concrete has gone far away from being brittle as it is used to be.